Performance of steel plate girders with inclined stiffeners - Mohd. Yazmil Md. Yatim,; M. R. Azmi,; M. Mukhlisin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Slender webs in steel plate girders are prone to local and shear buckling at relatively low shear and thus, need be stiffened to increase the strength and stability of the girders. The conventional way is to provide vertical stiffeners at specified intervals, but this practice serves only to prevent the buckling of web. Provision of inclined stiffeners, in addition to improving buckling resistance, forms a truss-like girder which allows those stiffeners to carry some percentages of forces exerted in the girder. This paper, therefore, presents the ultimate performance of thin-webbed plate girders containing inclined stiffeners. Five simply supported plate girders of practical size were tested to failure under concentrated load applied at the mid-span. This study focuses on the effects of different inclination angles of intermediate stiffeners,